Coming up for Air: On Reading in a Global Pandemic - Tarc, Aparna (Journal of the Canadian Association for Curriculum Studies, 2021)
The thought of breath grips the world as climate change, racial injustice and a global pandemic converge to suck oxygen, the lifeforce, out of the earth. The visibility of breath, its critical significance to existence, I argue, is made evident by poets. To speak of breath is to lodge ourselves between birth and death and requires sustained, meditative, attentive study to an everyday yet taken for granted practice. Like breathing, reading is also a practice that many took for granted until the pandemic. My paper will engage the affective and/or poetic dimensions of reading left out of theories of literacy that render it instrumental and divorced from the life of the reader (Freire, 1978). I will suggest that scholars of literacy, in every language, begin to engage a poetics of literacy as attending to the existential significance of language in carrying our personhood and lives. I will also argue that our diminishing capacities to read imaginatively and creatively have led to the rise of populist ideologies that infect public discourse and an increasingly anti-intellectual and depressed social sphere. Despite this decline in the practice and teaching of reading, it is reported that more than any other activity, reading sustained the lives of individuals and communities’ during a global pandemic. Teachers and scholars might take advantage of the renewed interested in reading to redeliver poetry and literary language to the public sphere to teach affective reading. Poetry harkens back to ancient practices of reading inherent in all traditions of reading. It enacts a pedagogy of breath, I argue, one that observes its significance in our capacity to exist through the exchange of air in words, an exchange of vital textual meanings we have taken for granted as we continue to infect our social and political world and earth with social hatred, toxins, and death. In this paper I engage fragments of poetry by poets of our time (last century onward) that teaches us to breathe and relearn the divine and primal stance that reading poetry attends to and demands. More than any other form, “poetry,” Ada Limon claims, “has breath built into it”. As such, reading poetry helps us to breathe when the world bears down and makes it hard for us to come up for air.